Comparison of subthalamic unilateral and bilateral theta burst deep brain stimulation in Parkinson’s disease - Gülke, Eileen; Horn, Martin A.; Caffier, Julian; Pinnschmidt, Hans; Hamel, Wolfgang; Moll, Christian K. E.; Gulberti, Alessandro; Pötter-Nerger, Monika (Frontiers in Human Neuroscience, 2023)
High-frequency, conventional deep brain stimulation (DBS) of the subthalamic nucleus (STN) in Parkinson's disease (PD) is usually applied bilaterally under the assumption of additive effects due to interhemispheric crosstalk. Theta burst stimulation (TBS-DBS) represents a new patterned stimulation mode with 5 Hz interburst and 200 Hz intraburst frequency, whose stimulation effects in a bilateral mode compared to unilateral are unknown. This single-center study evaluated acute motor effects of the most affected, contralateral body side in 17 PD patients with unilateral subthalamic TBS-DBS and 11 PD patients with bilateral TBS-DBS. Compared to therapy absence, both unilateral and bilateral TBS-DBS significantly improved (P<0.05) lateralized Movement Disorder Society-Unified Parkinson's Disease Rating Scale part III (MDS-UPDRS III) scores. Bilateral TBS-DBS revealed only slight, but not significant additional effects in comparison to unilateral TBS-DBS on total lateralized motor scores, but on the subitem lower limb rigidity. These results indicate that bilateral TBS-DBS has limited additive beneficial effects compared to unilateral TBS-DBS in the short term.